PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA PADA MATERI PERSAMAAN KONTINUITAS KELAS XI SMA MELALUI TES KEMAMPUAN RESPONDEN - Raden Hanna Rifani; Harun Imansyah; Heni Rusnayati; A. F. C. Wijaya (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
In a previous study, which observed and conducted in one of Senior High School in Bandung, using the tests and questionnaires regarding the continuity equation the result shows 60,53% (from the questionnaire) students answer that the continuity equation is difficult to deal with, and 52,71% students (test) students could not answer the test. The aim of this study is to know the learning obstacle of students using the respondent capably test in a continuity equation subject for XI high school students. The learning obstacle that has been studied is the epistemological is the limitation of student to understand the certain content of a particular subject. The method used in this study is a descriptive qualitative method using the history analysis approach in Respondent Capability Test. In this approach, the researchers formed questionnaires essay type in which includes the essential sub-subject from continuity equation. The result of the test shows that students are having epistemological learning obstacles in continuity equation, which include the understanding of ideal fluid observed from current type, incorrect in answering the velocity in the cross-sectional area in question, and could not indicate the volume flow rate given case questionnaire. Keywords: Learning obstacles, Respondent capability Test, Continuity equation.